Durability of RC slabs strengthened with prestressed CFRP laminate strips under different environmental and loading conditions - Correia, Luís (2017)
Over the last decades, researchers have been studying fibre reinforced polymer (FRP) materials and their advantages in retrofitting of existing structures. The externally bonded reinforcement (EBR) technique is the most common practice in improving existing reinforced concrete (RC) structures with carbon FRP (CFRP) materials. In this regard, several additional advantages have been reported to the use of prestressed CFRP materials, mainly strips. However, the experience with RC strengthening using prestressed EBR-CFRP materials is still limited. Some concerns regarding the efficiency of the technique still exist, especially the durability and the long-term behaviour. This work aims at contributing to the knowledge on durability of RC slabs strengthened with prestressed CFRP laminate strips according the EBR technique. The durability was studied by exposing strengthened RC specimens to the following environments for approximately 8 months: (i) reference environment – specimens kept in a climatic chamber at 20 ºC; (ii) water immersion in tank at 20 ºC of temperature; (iii) water immersion in tank with 3.5% of dissolved chlorides at 20 ºC of temperature; and (iv) wet/dry cycles in a tank with a water temperature of 20 ºC. Additionally, half of the specimens were subjected to sustained loading at a load level of 1/3 of the ultimate load, with the occurrence of cracking. After the exposure period the slabs were monotonically tested up to failure by using a four-point bending test configuration. The results showed that the environmental conditions and the sustained loading, separately or combined, led in general to slight losses of performance and ductility. Although these losses were subtle, considering that the tests were carried out for 8 months, clear indications are given towards the importance of conducting similar tests for longer periods. The results obtained showed that the procedures implemented to assess the durability of the strengthening systems were sensitive to the most relevant deterioration mechanisms and their impact on the mechanical properties of the specimens. Therefore, these procedures may well contribute for the future establishment of standardized test programmes for the assessment of the durability of prestressed CFRP strengthening systems.